(untitled) (Olhar de Professor, 2023)
This article approaches the proposition of BNCC and the proposal of human training present in this document. Based on qualitative and documentary research, the philosophical perspective of education in contemporary times is presented, supported by Paulo Freire, Boaventura de Sousa Santos and Edgar Morin, and the manifest and latent content informed in the BNCC document is studied. It is concluded that the training project intended by BNCC is averse to the agenda of changes and the educational reform required in the 21st century, which should encompass not only the contents and methods, but, mainly, the involvement of man in his totality, that is, in his rational, ethical and aesthetic aspects.